2019
DOI: 10.1017/s0144686x19001260
|View full text |Cite
|
Sign up to set email alerts
|

The role of individual resources, health behaviour and age perception as determinants of sports participation in older age

Abstract: Sports participation contributes to maintaining health and wellbeing in old age, hence a deeper understanding of its various determinants is necessary. Previous research has primarily focused on either the effects of individual resources or age-specific attitudes to sports participation. However, a deeper understanding of the inter-relationships between these variables is required to develop effective policies to promote sports participation in ageing societies. To address the hypothesised inter-relationships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
1
8
2
Order By: Relevance
“…The significant results surrounding number of health conditions and social influences suggest that those with a higher number of health conditions rate social interactions as being more influential on the initiation of walking football (see figure 1). Regarding SES, gender and weekly PA results, this contradicts previous research into sport participation in older adults, specifically concerning gender differences and SES differences which have previously been seen amongst those participating in older adulthood (Faß & Schlesinger, 2019). Possible explanations for the inconsistency between previous research and this study may lie in the group characteristics, the sport context assessed, and the imbalance between male and female respondents.…”
Section: Differences In Walking Football Initiation and Maintenance I...contrasting
confidence: 99%
See 1 more Smart Citation
“…The significant results surrounding number of health conditions and social influences suggest that those with a higher number of health conditions rate social interactions as being more influential on the initiation of walking football (see figure 1). Regarding SES, gender and weekly PA results, this contradicts previous research into sport participation in older adults, specifically concerning gender differences and SES differences which have previously been seen amongst those participating in older adulthood (Faß & Schlesinger, 2019). Possible explanations for the inconsistency between previous research and this study may lie in the group characteristics, the sport context assessed, and the imbalance between male and female respondents.…”
Section: Differences In Walking Football Initiation and Maintenance I...contrasting
confidence: 99%
“…Possible explanations for the inconsistency between previous research and this study may lie in the group characteristics, the sport context assessed, and the imbalance between male and female respondents. Firstly, within this population, influences of walking football initiation may not be affected by gender or SES level, as it may be in a wider sport participation context (Faß & Schlesinger, 2019). Secondly, walking football is a recently developed adapted sport, and it is possible that sport type and intensity may provide less variation in the influences assessed among these groups.…”
Section: Differences In Walking Football Initiation and Maintenance I...mentioning
confidence: 97%
“…No evidence was found to suggest that initiation influences differ across gender, SES or weekly PA levels, but significant results were found when assessing initiation influences by number of health conditions. Regarding SES, gender and weekly PA results, this contradicts previous research into sport participation in older adults, specifically concerning gender differences and SES differences which have previously been seen amongst those participating in older adulthood (Faß & Schlesinger, 2019). Possible explanations for the inconsistency between previous research and this study may lie in the group characteristics, the sport context assessed, and the imbalance between male and female respondents.…”
Section: Differences In Walking Football Initiation and Maintenance Influences Across Gender Ses Number Of Health Conditions And Weekly Pcontrasting
confidence: 99%
“…To help understand how to offset the decline in sport participation in older adulthood, research within the field of psychology and behaviour change has started to explore the determinants and barriers associated with sport participation. Studies have found multiple factors related to participation in sport, often involving individual level influences, social facilitators and environmental factors (Faß & Schlesinger, 2019;Henderson et al, 2012;Jenkin et al, 2017;Kolt et al, 2004;. .…”
Section: Mainstream Sport Participation In Older Adulthoodmentioning
confidence: 99%
“…In addition, 689 people older than 60 years with a good education adopted significantly stronger health behaviours [ 20 ]. These studies express the idea that a higher educational level can make individuals consider sport as an unavoidable part of health, and hence, its practice is associated with the search for better living conditions [ 35 ]. Despite what has been said, these results do not correspond to the differences in the level of physical activity practiced, as is the case in the current publication, which considers physically active older people and differentiates their high or low-to-moderate level of physical activity based on their educational level.…”
Section: Discussionmentioning
confidence: 99%